Active media technology : (World Scientific, 2003)
This book captures the essence of the current state of research in active media technology and identifies the new changes and opportunities — both current and future — in the field. Distinguished researchers such as Prof Ning Zhong from the Maebashi Institute of Technology, Prof John Yen from the Pennsylvania State University, and Prof Sanker K Pal from the Indian Statistical Institute present their research papers.